Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18116106
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations between Intake of Fruit and Vegetables and Height Attainment from Preschool to School Entry

Abstract: To examine associations between fruit and vegetable intake in young childhood and height attainment during preschool and at school entry. Data for this study was based on “The Healthy Start” primary intervention study, which included 635 obesity-prone children, (58% boys), from the greater Copenhagen area, with a mean (SD) age of 4.0 (1.1) years (age range 2–6 years) at baseline. In the current study, 553 children (57% boys) were included with information on dietary intake at baseline and height measured at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(71 reference statements)
1
0
0
Order By: Relevance
“…In this representative study, higher intakes of vegetables (in women) and F&V (both in men and women) were directly associated with a greater height after adjustment for age, level of education, BMI, family structure, and income. This is in accordance with a former study that found direct associations between fruit and vegetables intake with height attainment during childhood (Rosário et al, 2021). We know that current fruit and vegetables intake might differ from previous intakes.…”
Section: Discussionsupporting
confidence: 94%
“…In this representative study, higher intakes of vegetables (in women) and F&V (both in men and women) were directly associated with a greater height after adjustment for age, level of education, BMI, family structure, and income. This is in accordance with a former study that found direct associations between fruit and vegetables intake with height attainment during childhood (Rosário et al, 2021). We know that current fruit and vegetables intake might differ from previous intakes.…”
Section: Discussionsupporting
confidence: 94%